Manual de atividades lúdicas: educação alimentar e nutricional na atenção primária à saúde - SOUSA, Fabiana Nunes de (2023)
Introduction: Primary Health Care is considered a privileged sector for the application of preventive and educational measures. Among these, Food and Nutrition Education is an indispensable tool, especially in working with children, becoming more efficient from the planning of playful and dynamic actions, which can use technological devices as facilitating instruments. Thus, the manual stands out as an instructive Educational Technology that aims to share information capable of guiding health professionals in the application of Food and Nutrition Education for children. Objectives: To elaborate a ludic activities manual of food and nutrition education in PHC. Method: To prepare the manual, Food and Nutrition Education activities previously developed and applied by the extension project team at the Federal University of Pará were used: “Health workshop: Food and Nutrition Education Actions for Children in Primary Health Care” in a Municipal Health Unit. Health in the Guamá neighborhood, in Belém, Pará, from March 2019 to February 2020. Results: The manual in its final form has 33 pages where 10 activities of Food and Nutrition Education are presented. The design of the Educational Technology was based on the association of vibrant colors with minimalist visual elements in order to make reading more attractive. Conclusion: From the preparation of the manual, it was possible to highlight the relevance of this type of Educational Technology and its functionality as a simplifying apparatus for the development of Food and Nutrition Education actions, as well as the importance of the debate on the topics addressed for empowerment and development of autonomy of the child audience. Thus, the applicability of the manual in Primary Health Care is emphasized due to the relevance of such sector for the execution of educational actions, in which the tool in question presents itself as an important facilitating tool during their planning.